Индивидуальные особенности петербургского пролога 13.8.2 - Владимировна Чистякова, Марина (Slavistica Vilnensis, 2009)
The goal of this study is to explore the structural features of Prolog No. 13.8.2 on the basis of the materials collected over three autumn months. The manuscript dates back to the third quarter of the sixteenth century and is now deposited in the St. Petersburg Library of the Russian Academy of Sciences. The author identifies innovative individual texts in the structure of the codex. Their analysis leads to the conclusion that this prolog must have been compiled by parish church clerks (i.e. outside the monastic environment). The calendar order of certain traditional prolog texts, both instructive stories and lives of saints, has been changed. In their first and second editions a simple pro log was used to compile Manuscript No. 13.8.2. The language and orthography of the manuscript reveal its Ukrainian origin. Although the prolog was written in Church Slavonic, some texts contain Ruthenian lexicon, e.g. the lives of St. Cosmas and St. Damian. The prolog also contains later editorial corrections made by another person after the manuscript had been written.